Morphological and molecular data for species of Lecithaster Lühe, 1901 and Hysterolecithoides Yamaguti, 1934 (Digenea: Lecithasteridae) from fish of East Asia and phylogenetic relationships within the Hemiuroidea Looss, 1899. (2020) - Atopkin, D.M.; Nakao, M.; Besprozvannykh, V.V.; Ha, N.D.; Nguyen, H.V.; Sasaki, M.
Abstract: Four representatives of the genus Lecithaster and one representative of the genus Hysterolecithoides were found during investigation of the trematode fauna of fish species in Vietnamese, Japanese and eastern coastal waters of the Russian Far East. Based on morphometric data, adult trematodes from Vietnamese Strongylura strongylura and Russian Acanthogobius flavimanus were identified as Lecithaster confusus, trematodes from Vietnamese Hemirhamphus marginatus as L . sayori and from osmerid fishes as L . salmonis . Further, a single specimen of Lecithaster sp. and representatives of Hysterolecithoides epinepheli were found in Vietnamese Siganus fuscescens. Morphological and molecular data, including 18S ribosomal DNA (rDNA) V4 fragment, 28S rDNA D1-D3 fragment, internal transcribed spacers (ITS) and a mitochondrial COI gene fragment were analysed for Lecithaster spp. The results revealed that L . sayori and L . salmonis are not synonyms of L . stellatus and L . gibbosus, respectively, but that Hysterolecithoides frontilatus and H. guangdongensis are junior synonyms of H . epinepheli. The 28S-rDNA-based phylogenetic tree of Hemiuroidea showed a distinct position for the genus Lecithaster with internal differentiation into three subclades, including L . confusus, L . sayori and Lecithaster sp. within the first subclade, L . mugilis and L . sudzuhensis within the second subclade and L . salmonis and L . gibbosus within the third subclade. Bayesian phylogenetic reconstructions of Hemiuroidea showed four clades for members of Hemiuridae and Lecithasteridae. The first clade consisted of Hemiuridae representatives and the second clade represented the genus Lecithaster . The third clade included genera Aponurus and Lecithophyllum (Lecithasteridae) and the fourth clade combined members of lecithasterid Quadrifoliovariinae and Hysterolecithinae and hemiurid Opisthadeninae and Bunocotylidae with high statistical support.